2014
DOI: 10.1364/ao.53.008167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of constructional parameters on the performance of a surface plasmon resonance sensor based on a multimode polymer optical fiber

Abstract: We experimentally studied the influence of different constructional parameters on the performance of surface plasmon resonance (SPR) sensors based on a commercially available polymer step-index multimode fiber. For the first time, to the best of our knowledge, we experimentally investigated the influence of polishing depth on the characteristics of SPR sensors based on a straight multimode fiber. We also examined the impact of sensing length on the spectral position and strength of the SPR in side-polished str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Feasibility of bent MOF SPR sensors have also been theoretically investigated for potential performance improvement, tunable by bending [ 63 ]. However, a recent experimental study, comparing bent and straight side-polished SPR probes revealed no significant improvement for the bent SPR fiber (bent radii of 10, 15 and 20 mm) compared with a straight side-polished one [ 64 ].…”
Section: Plasmonic Fiber Sensor Designsmentioning
confidence: 99%
“…Feasibility of bent MOF SPR sensors have also been theoretically investigated for potential performance improvement, tunable by bending [ 63 ]. However, a recent experimental study, comparing bent and straight side-polished SPR probes revealed no significant improvement for the bent SPR fiber (bent radii of 10, 15 and 20 mm) compared with a straight side-polished one [ 64 ].…”
Section: Plasmonic Fiber Sensor Designsmentioning
confidence: 99%
“…Consequently, the bending induced deformation of the external layer of the cladding, which scales up with the fibre diameter, is a few times lower in the fibres reported in this work compared to Ref. 28, thus giving a practically null impact on the sensors sensitivity.…”
Section: Resultsmentioning
confidence: 56%
“…In our previous work [28], a small dependence of the sensitivity upon a bending radius was reported. This discrepancy is related to a greater diame− ter of the fibre used for fabrication of the sensors reported in Ref.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Variations in RI of the ambient environment would affect the wavelength at which this plasmon absorption occurs resulting in a variation in resonant wavelength of the absorption bands [139]. Such SPR sensing probes have been mainly used as RI sensors and have been demonstrated using etched fibers [138,140], side polished fibers [139,141,142] and also through the deposition of gold nanoparticles onto the end-face of an optical fiber [143].…”
Section: Metallic Layer Fiber Claddingmentioning
confidence: 99%